The Propagation of Landslide-Generated Impulse Waves and Their Impacts on the Moored Ships: An Experimental Investigation. (12th May 2020) - Mu, Ping; Wang, Pingyi; Han, Linfeng; Wang, Meili; Meng, Caixia; Cheng, Zhiyou; Xu, Haiyong
Abstract : The effective prevention and reduction of the hazardous impact of landslide-generated impulse waves on the moored ships are crucial for the sustainable operation of the reservoirs. Although the investigations of landslide-generated impulse waves have been widely studied in the past decades, few efforts involved their impacts on the moored ships. The authors in this paper specifically examine the hazardous impact of the impulse waves on the moored ships by applying the physical experiments. Considering that the impulse wave was an external force acting on the mooring line, the impulse wave generation, propagation, and its impact on the moored ships are hence explored in detail. The results indicate that the impact of impulse waves on the moored ships was mainly due to the first wave amplitude and height, and an exponential function relationship between the relative wave height and wave crest amplitude was revealed. Furthermore, the attenuation of the maximum wave crest amplitude was approximated by a power exponential function. On this basis, the mooring tension could be calculated based on the linear relationship between the mooring tension and wave height. Ultimately, the safety of the moored ships in the port can be evaluated.